Nutritional and Antioxidant Variability of Some Wild and Cultivated Edible Mushrooms from Kastamonu Rural Areas - Turfan, Nezahat; Ayan, Sezgin; Akın, Şeyma Selin; Akın, Enes (Turkish Science and Technology Publishing (TURSTEP), 2019)
In this study, variation of some chemical components such as anthocyanin, β-carotene, lycopene, phenolic, nitrate, soluble protein, proline, glucose, sucrose and total carbohydrate level ad PAL activity in some wild and cultivated edible mushrooms was examined. For this, four different mushroom species (Agaricus campestris L., Cantharellus cibarius Fr., Hericium erinaceus (Bull.) Pers., Lactarius piperatus L. Pers) were supplied from local market, named Kuzeykent Semt Bazaar, in Kastamonu province of Turkey. Mushroom samples were collected from Araç, Daday, Devrekani and Tosya locations of Kastamonu. According to findings, the highest anthocyanin value and PAL activity were obtained from A. campestris collected from Arac location with 0.107 mg g-1 and 6.99 EU, respectively. The amount of β-carotene (2.297 mg g-1) and lycopene (0.644 mg g-1) was the highest in C. cibarius collected from Tosya location, however; proline, soluble protein, nitrate and glucose level were the maximum in A. campestris collected from Devrekani location with 149.61 Âµmol g-1, 55.49 mg, 159.963 mg g-1 and 29.36 Âµg g-1, respectively. While total carbohydrate was the highest in H. erinaceus collected from Araç location with 80.97 Âµg g-1, sucrose concentration was the maximum with 39.22 mg g-1 in H. erinaceus collected from Daday location. As a result, A. campestris collected from Devrekani location exhibited the highest nutrient in terms of chemicals analysed except anthocyanin and it was followed by H. erinaceus collected from Daday location. However, C. cibarius and H. erinaceus collected from Araç location had lower chemical components. It can be said that these mushroom species are valuable and important as major food sources and non-wood products for Kastamonu province.
Keywords: antioxidants; kastamonu; nutrients; S; Agriculture (General); turkey; Agriculture; mushrooms; S1-972